How the future of the global forest sink depends on timber demand, forest management, and carbon policies. (September 2022) - Daigneault, Adam; Baker, Justin S.; Guo, Jinggang; Lauri, Pekka; Favero, Alice; Forsell, Nicklas; Johnston, Craig; Ohrel, Sara B.; Sohngen, Brent
Highlights: Global forest sector model intercomparison of 81 future pathway scenarios. Socioeconomic drivers have strongly influence forest sector model estimates. Global forests could sequester 1.2–5.8 GtCO2e/yr over the next century. Improved management can increase carbon and harvests without expanding forest area. Climate policy assessments could better represent forest markets and management dynamics. Abstract: Deforestation has contributed significantly to net greenhouse gas emissions, but slowing deforestation, regrowing forests and other ecosystem processes have made forests a net sink. Deforestation will still influence future carbon fluxes, but the role of forest growth through aging, management, and other silvicultural inputs on future carbon fluxes are critically important but not always recognized by bookkeeping and integrated assessment models. When projecting the future, it is vital to capture how management processes affect carbon storage in ecosystems and wood products. This study uses multiple global forest sector models to project forest carbon impacts across 81 shared socioeconomic (SSP) and climate mitigation pathway scenarios. We illustrate the importance of modeling management decisions in existing forests in response to changing demands for land resources, wood products and carbon. Although the models vary in key attributes, there is general agreement across a majority of scenarios that the global forest sector could remain a carbon sink in the future, sequestering 1.2–5.8 GtCO2e/yr over the next century. Carbon fluxes in the baseline scenarios that exclude climate mitigation policy ranged from −0.8 to 4.9 GtCO2e/yr, highlighting the strong influence of SSPs on forest sector model estimates. Improved forest management can jointly increase carbon stocks and harvests without expanding forest area, suggesting that carbon fluxes from managed forests systems deserve more careful consideration by the climate policy community.